The Influence of Role Conflict and Role Ambiguity on Trainee Non-Disclosure (Trainee Disclosure and Trainee Anxiety) among Trainee Counsellors in Malaysia - Anis Natasha, Zulkifli; Nor Mazlina, Ghazali; Edris, Aden (2022)
This study examined the influence of role conflict and role ambiguity on trainee non- disclosure (trainee disclosure and trainee anxiety) among trainee counsellors in Malaysia. In this chapter, some aspect would be covered such as research background, problem statement, research objectives, research questions, research hypothesizes, significance study and definition of term. From this research, the future direction is the line of research would like provide information on changes in these variables over course of supervision, as well as information on how the influence between role conflict and role ambiguity might change over the trainee nondisclosure experiences. This research focused on influence of role conflict and role ambiguity on trainee non- disclosure in supervision process. This is because an effective supervision between supervisor and supervisee which is trainee counsellor would be generated by willingness to disclose. Trainee counsellor faced the difficulties in order to disclose any issues with their supervisor. Thus, it is giving a negative effect in supervision session between supervisor and trainee counsellor. This research extends the knowledge and understanding on trainee counselor in supervision session that may influence the role conflict and role ambiguity that lead to trainee non-disclosure among them.